Evaluating the development of technopreneurs: a case study of PPR Telecenter Jalan Jelatek - Mohd Asruladlyi Ibrahim,; Jalaluddin Abdul Malek,; Ali Salman, (Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
Bridging Digital Divide (BDD) is aimed to bridge digital between those who affluent with information and those who don’t ,thus increasing the socioeconomic status of Malaysians . Telecentre is one of the method used by the government to bridge the digital gap in Malaysia. Issues and matters of this study are how far the effectiveness of telecentre in helping to bridge the digital gap and developed techopreneur for PPR residents in Jalan Jelatek as well as increasing their sosioeconomic. Data were collected through interview and observation. Cumulative data were analysed in descriptive. A total of 20 internet entrepreneurs were selected as respondents. The study found that this programme is capable to give big impact on the socio-economic community, especially for those who know how to seize the opportunity of ICT.